Generation and application of mammalian haploid embryonic stem cells. (3rd May 2016) - Bai, M.; Wu, Y.; Li, J.
Abstract: Haploid cells contain one set of chromosomes and are amenable for genetic analyses. In mammals, haploidy exists only in gametes. An intriguing question is whether haploid cells can be derived from gametes. Recently, by application of haploid cell enrichment using fluorescence‐activated cell sorting, stable haploid embryonic stem cells (haESCs) have been successfully derived from oocyte‐derived parthenogenetic and sperm‐derived androgenetic embryos from several species. Whilst both parthenogenetic and androgenetic (AG)‐haESCs enable whole‐genome genetic screening at the cellular level, such as screening of drug resistance or disease‐related genes, AG‐haESCs, after intracytoplasmic injection into oocytes, can also be used to produce alive semi‐cloned mice. Nevertheless, one major drawback associated with wild‐type AG‐haESCs is the very low birth rate of healthy semi‐cloned mice. Of interest, after inhibiting the expression of two paternally imprinted genes ( H19 and Gtl2 ) in AG‐haESCs by removal of their differentially DNA methylated regions, double‐knockout AG‐haESCs can efficiently and stably support the generation of healthy semi‐cloned pups. Importantly, double‐knockout AG‐haESCs are feasible for multiple genetic manipulations, followed by efficient generation of semi‐cloned mice carrying multiple genetic traits; thus they could be used to validate candidate loci that have been identified in genome‐wide association studies of multigenic diseases by generation of mouse models carrying multiple alterations. Of note, by combining a CRISPR‐Cas9 library and double‐knockout AG‐haESCs, semi‐cloned mice carrying different mutant genes can be efficiently generated in one step, enabling functional mutagenic screening in mice. HaESCs, therefore, provide a powerful tool for genetic analyses in mammals at both the cellular and organismal levels. Abstract : Content List – Read more articles from the symposium: Human models and technology for regenerative medicine.